Moisture Absorption and Desorption in an Ionomer-Based Encapsulant: A Type of Self-Breathing Encapsulant for CIGS Thin-Film PV Modules. (December 2020) - Yang, Miao; Schäffler, Raymund; Repmann, Tobias; Orgassa, Kay
Abstract: As an alternative to conventional encapsulation concepts for a double glass photovoltaic (PV) module, we introduce an innovative ionomer-based multi-layer encapsulant, by which the application of additional edge sealing to prevent moisture penetration is not required. The spontaneous moisture absorption and desorption of this encapsulant and its raw materials, poly (ethylene- co -acrylic acid) and an ionomer, are analyzed under different climatic conditions in this work. The relative air humidity is thermodynamically the driving force for these inverse processes and determines the corresponding equilibrium moisture content (EMC). Higher air humidity results in a larger EMC. The homogenization of the absorbed water molecules is a diffusion-controlled process, in which temperature plays a dominant role. Nevertheless, the diffusion coefficient at a higher temperature is still relatively low. Hence, under normal climatic conditions for the application of PV modules, we believe that the investigated ionomer-based encapsulant can "breathe" the humidity: During the day, when there is higher relative humidity, it "inhales" (absorbs) moisture and restrains it within the outer edge of the module; then at night, when there is a lower relative humidity, it "exhales" (desorbs) the moisture. In this way, the encapsulant protects the cell from moisture ingress.